(3fRgI GdCfGe aj JGQjN GdESdGes - (3EHQGgje Hf eMeO Hf CjOeQ GdYdGFj GdSQGLj, GHf ObeGb , UGQe GdOjf ,J (B809 (3g` s ((3CMeO Hf YHO GdMejO Hf eMeO GdeYQha HGdeUQi s)
(3ChdgG (B:s
(3jHJOF HSfI (B279(3g` s
(3BNQgG (B:s
(3jfJgi HCKfGA hajGJ SfI (B422(3g` s
(3jONd aI gPG GdeLdO bWYI ef cJGH Yjhf GdJhGQjNs
(3Ke bWYI CNQi ef fRgI GdCfGe GdePchQs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B64 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B86s
Keywords: (3GdJGQjNs